The relationship between pre-operative right ventricular longitudinal strain and low-cardiac-output syndrome after surgical aortic valve replacement - Zhang, Yong-jian; Chen, Hong; Dong, Ya-ling; Shang, Jia-nan; Ruan, Li-tao; Yan, Yang; Song, Yan (Frontiers in Cardiovascular Medicine, 2023)
Objectives This study was performed to investigate the relationship between right ventricular free wall longitudinal strain (RVFWSL) and low cardiac output syndrome (LCOS) after surgical aortic valve replacement (SAVR) and to further explore its association with readmission within 2 years in patients who developed LCOS after SAVR. Methods This single-center retrospective observational study involved consecutive patients who underwent SAVR at our hospital from May 2018 to June 2020. Preoperative echocardiography was obtained within 3 days before SAVR. The longitudinal strain of the right ventricle was analyzed using the right ventricle as the main section, and the RVFWSL and right ventricular four-chamber longitudinal strain (RV4CSL) were obtained. The primary observation was the occurrence of LCOS. The secondary prognostic indicators were mainly the readmission rates within 2 years. Results In total, 146 patients were finally included in this study. The RVFWSL was significantly lower in the LCOS group than in the No-LCOS group（16.63 ± 2.10）vs.（23.95 ± 6.33）, respectively; P < 0.001). The multivariate regression analysis showed that the RVFWSL was associated with LCOS (odds ratio, 1.676; 95% confidence interval, 1.258–2.232; P < 0.001). The receiver operating characteristic curve showed that the cut-off value for RVFWSL to predict LCOS was less than −18.3, with an area under the curve of 0.879, sensitivity of 100%, and specificity of 80.47%. The multivariate regression analysis showed that LCOS was an independent risk factor for readmission within 2 years in patients undergoing SAVR. Conclusions Patients with RVFWSL (<−18.3%) may be an increased risker for LCOS after SAVR. The occurrence of LCOS after SAVR is a risk factor for readmission within 2 years. Right ventricular function monitoring may have some predictive value for the postoperative prognosis in patients undergoing SAVR.